Strategi Komunikasi Komisi Pemilihan Umum Kabupaten Bantul dalam Sosialisasi Pelaksanaan Pemilihan Kepala Daerah Saat Pandemi Covid-19 Tahun 2020 - Eka Anisa Sari; Muhammad Rifa'at Adiakarti Farid (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2021)
This study discusses the communication strategy of the Bantul General Election Commission in disseminating the implementation of Regional Head Elections during the Covid-19 Pandemic. The background of this research because the Regional Head Election (Pilkada) was held in the midst of the Covid-19 pandemic, which spreads very quickly from human to human, so the government urges to maintain distance to prevent the transmission and spread of Covid-19. Pilkada which is actually a people's democratic party which usually gathers a lot of masses to get support. This study used descriptive qualitative method. The results of the study show that all stages of the elections carried out by the KPU Bantul are in accordance with PKPU Number 5 of 2020, by implementing health protocols and conducting online and offline socialization involving all elements of election organizers as well as regional stakeholders make the voters lead to high voters turnout in Bantul.